The role of followership in enhancing teachers’ organizational commitment dimensions - Othman, Cammellia; Busari, Abdul Halim; Sulong, Majelan (Journal of Education and Learning (EduLearn), 2025)
This study explores the relationship between followership and three dimensions of organizational commitment: affective, normative and continuance among primary school teachers in Sarawak, Malaysia. Research on how followership behaviours affect employee commitment is weak despite increased understanding of their role in organisational success. To fill this gap, the study surveyed 899 primary school teachers using the revised kelley followership questionnaire (KFQ-R) and the three-component model employee commitment survey (TCM-ECS). Data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results demonstrate significant positive relationships between followership and all three commitment dimensions, with the strongest association observed for affective commitment (β=0.564, p0.001), followed by normative commitment (β=0.388, p0.001) and continuance commitment (β=0.337, p0.001). These findings suggest that effective follower behaviors significantly enhance employees’ emotional attachment, sense of obligation and perceived cost of leaving their organizations. Although this is cross-sectional research, it adds to our understanding of how followership may assist establish organizational loyalty. It also suggests that organizations may be able to increase employee commitment by teaching people how to follow others.